Memory T Cells - Zanetti, Maurizio; Schoenberger, Stephen P.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Immunological memory has fascinated microbiologists and immunologists for decades as one of the new frontiers to conquer to better understand the response to pathogens, cancer and vaccination. Over the past decade, attention has turned to the intrinsic properties of the memory T cells themselves, as it has become clear that the eradication of both infected cells and tumors requires T cells. This book is an attempt to capture the wave of discoveries associated with these recent studies. Its chapters represent a wide collection of topics related to memory T cells by laboratories that have invested their skills and knowledge to understand the biology and the principles upon which memory T cells are generated, maintained and expanded upon re-encounter with antigen. Ultimately, these studies are all aimed at a better understanding of the function of memory T cells in protection against disease.
Memory Th1/Th2 Cell Generation Controlled by Schnurri-2 -- Transcriptional Regulation during CD8 T-Cell Immune Responses -- The Role of Interleukin-2 in Memory CD8 Cell Differentiation -- The Role of Inflammation in the Generation and Maintenance of Memory T Cells -- The Role of OX40 (CD134) in T-Cell Memory Generation -- The Role of Precursor Frequency in the Differentiation of Memory T Cells: Memory by Numbers -- CD8 T-Cell Memory Differentiation during Acute and Chronic Viral Infections -- Longevity of T-Cell Memory following Acute Viral Infection -- Principles of Memory CD8 T-Cells Generation in Relation to Protective Immunity -- Memory T Cells in Rhesus Macaques -- Memory T-Cell Subsets in Parasitic Infections -- Antigen Specific Memory T Cells and Their Putative Need for the Generation of Sustained Anti-Tumor Responses -- Memory T-Cell Responses and Survival in Human Cancer: Remember to Stay Alive -- Analysis of Vaccine-Induced T Cells in Humans with Cancer -- Memory T-Cell Homeostasis and Senescence during Aging.
Keywords: Medicine; Neurochemistry; Biomedicine; Molecular Medicine; Neurochemistry